My friend Doggie; or, An only child - Glasgow, G. R. (Geraldine Robertson) (Salt Lake City, UT : Project Gutenberg, 2025)
"My Friend Doggie; or, An Only Child" by G. R. Glasgow is a charming children's story written in the early 20th century. The book explores themes of friendship, generosity, and the innocence of childhood through the interactions between a little girl from a privileged background and a boy from a less affluent family. It portrays the values of love and kindness that transcend social class. The narrative revolves around Bet, a young boy who embodies mischief and plainness yet possesses a generous heart. He forms a bond with Miss Dolly, a lovely girl who shows bravery when she defends his kitty from some rough boys. In an act of selflessness, Bet decides to give his beloved puppy as a Christmas gift to Dolly, showcasing the depth of his feelings and the importance of friendship. As the story unfolds, it highlights the joy of simple acts of kindness and the meaningful connections formed between children, ultimately portraying a heartwarming tale of love that unites different worlds. (This is an automatically generated summary.)
Release date is 2025-02-25
Bob Taylor, Mairi and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Children's stories; Children -- Conduct of life -- Juvenile fiction; Christmas -- Juvenile fiction; Pets -- Juvenile fiction; Gifts -- Juvenile fiction